pengaruh Pengaruh Profitabilitas, Leverage, Kesempatan Investasi, Tax Avoidance, dan Kepemilikan Manajerial terhadap Kebijakan Dividen dengan Likuiditas sebagai Variabel Moderasi pada Perusahaan Sektor Property dan Real Estate yang terdaftar di Bursa Efek Indonesi - Saadatul Abadiyah; Trias Madanika Kusumaningrum (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
This research studies the relationship between profitability, leverage, Investment opportunity set, tax avoidance and managerial ownership on dividend policy and to determine whether liquidity can be a moderating variable between the effect of profitability, leverage, Investment opportunity set, tax avoidance and managerial ownership on dividend policy. The sample of this study consisted of 15 companies confirmed by the Indonesia Stock Exchange in property and real estate from 2018–2021. The sampling technique used purposive sampling. The analysis technique uses path analysis with STATA 17. Before using the path analysis, we must make the test assumption of normality, multicollinearity, heteroscedasticity, and autocorrelation. The research found no significant effect on profitability, leverage, investment opportunity set, tax avoidance and managerial ownership on dividend policy. Liquidity was found to be moderating variables for profitability, tax avoidance and investment opportunity set on dividend policy. While in the test, liquidity can’t be moderating variable for leverage and managerial ownership on dividend policy